Analysis of the Influence of Korean Boybands on Teenagers in the Bandung Region in the Perspective of Cultural Imperialism - Tedi Kurniadi; Chyntania Chantika Triana (Trigin Publisher, 2020)
The rapid flow of globalization has made foreign cultures enter through several mass media platforms supported by very easy internet access. Including kpop culture that enters and spreads among teenagers, children, especially students. Kpop culture is often associated with consumerism because of the level of spending money on kpop goods regularly in a certain period of time. The purpose of this study is to determine the impact of the phenomenon of kpop culture on the socio-economic and cultural aspects but here we will emphasize the cultural aspect. The method in this study is a quantitative method with questionnaire data collection. We will conduct research in Bandung area which is prone to be affected by the surrounding environment.